Self-Reported Training and Supplementation Practices Between Performance-Enhancing Drug-User Bodybuilders Compared with Natural Bodybuilders. Issue 5 (22nd May 2023) - Li, Jiuzhang; Davies, Timothy B.; Hackett, Daniel A.
Abstract: Li, J, Davies, TB, and Hackett, DA. Self-reported training and supplementation practices between performance-enhancing drug-user bodybuilders compared with natural bodybuilders. J Strength Cond Res 37(5): 1079–1088, 2023—This study aimed to examine whether the training and supplementation practices differ between performance-enhancing drug (PED)-using bodybuilders (BB) and natural BB. One hundred eighty-seven competitive male bodybuilders with a median age of 27.0 years completed an online survey. Of this sample, 40 respondents reported using PED (PED-user) and 147 respondents reported to be natural. Compared with natural BB, PED-user BB reported greater off-season body weight ( p < 0.001) and weight loss before a competition ( p < 0.001). In the off-season, PED-user BB performed a greater number of exercises per muscle group ( p < 0.001), number of repetition maximum (RM) per set ( p < 0.01), and less recovery between the sets ( p < 0.01). During the precompetition phase, the natural BB increased their number of RM; however, the PED-user BB still reported using a greater number of RM per set ( p = 0.02), exercises per muscle group ( p < 0.001), and less recovery time between the sets ( p < 0.01). Both the PED-user BB and natural BB reported greater aerobic exercise frequency ( p < 0.001) and session duration ( p < 0.001), although PED-user BB performed a greater number of aerobic exercise sessions ( p = 0.04) and at a higher intensity ( p < 0.01). Advanced training techniques, including negatives, partial repetitions, preexhaustion sets, and timed repetitions, were more popular among PED-user BB ( p < 0.05). Creatine monohydrate usage was more popular among natural BB ( p < 0.001), whereas branched-chain and essential amino acids were more popular among PED-user BB ( p ≤ 0.001). Findings suggest that PED-user BB perform more metabolically demanding resistance training sessions, more strenuous aerobic training during the precompetition phase, and may have different supplementation preferences compared with natural BB.